Modelling of breakthrough curve in water adsorption on silica gel and zeolite 4A - Andrés Rivera Guerrero; Gerardo Rodríguez Niño; Pedro Bejarano Jiménez (Revista Facultad de Ingeniería Universidad de Antioquia, 2014)
This  paper  presents  the  development  of  a  computational  model  to  simulate  the adsorption of water in a fixed bed, comparing the performance of zeolite 4A and silica gel type ‘A’. A variation of the Langmuir isotherm for zeolite 4A and Tóth isotherm for the silica gel were used; Linear Driving Force (LDF) model was used for adsorption rate with an overall coefficient temperature dependent.  The  model  is  composed  of  five  partial  differential  equations associated  with  mole  fraction  of  water,  temperature,  pressure,  superficial velocity  and  water  loading.  Method  of  lines  (MOL)  was  used  with  the  function ODE15S of Matlab® to solve the system. As response variables the characteristic time interval of the breakthrough curve, asymmetry, maximum temperature  and  pressure  drop,  through  a  two-level  factorial  scheme  were  evaluated.  Adsorbent  was  the  most  influential  variable  on  the  response variables.  Zeolite  has  the  highest  rate  of  adsorption  due  to  the  shape  of  the  adsorption  isotherm,  but  has  a  lower  water  retention  loading  and  increased  resistance to mass transfer.